The Impact of International Marketing Capabilities and Export Operations Capabilities on the Strategic Performance of Cross-Border E-Commerce with the Mediating Role of Information Technology Capabilities - Jahanbin, Tina; Rostamijo, Mohammad Saman; Hadi, Seyedeh Sara; Hassas, Nasim Sadat; Vaseinia, Homa (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The aim of this study is to examine the impact of international marketing capabilities and export operations capabilities on the strategic performance of cross-border e-commerce, considering the mediating role of information technology capabilities.Methodology: This research is applied in purpose and descriptive-survey in nature for data collection. The statistical population consists of managers of small- and medium-sized businesses engaged in online exports in Tehran. Based on the Krejcie and Morgan table, a total of 207 valid questionnaires were obtained through simple random sampling. Field data were collected using the questionnaires developed by Casillas and Magno (2022) and Catanzaro and Tesser (2020). The validity of the questionnaire was confirmed using face and content validity, while its reliability was established through Cronbach's alpha. SPSS and Smart PLS software were used for data analysis.Findings: The findings revealed that international marketing capabilities and export operations capabilities have a significant impact on both the strategic performance of cross-border e-commerce and information technology capabilities. Additionally, information technology capabilities were found to have a significant impact on the strategic performance of cross-border e-commerce. Furthermore, the mediating role of information technology capabilities in the relationship between international marketing capabilities, export operations capabilities, and the strategic performance of cross-border e-commerce was confirmed.Conclusion: Developing global business relationships and establishing international distribution networks enable companies to reach more customers and increase their sales volumes. By analyzing market conditions and anticipating risks, companies can develop appropriate strategies to address challenges. International marketing capabilities also contribute to creating a sustainable competitive advantage in global markets.